Tahlil al-Qiyam al-Akhlaqiyyah fi Asy’ar Qashr al-Malik Banggai li Habib Aydarus: Dirasah Simiya’iyyah ʻInda Michael Riffatere/ Analysis of Moral Values in the Poem Qashr al-Malik Banggai by Habib Idrus: A Semiotic Study by Michael Riffatere - Qadhil Amin Sahupala; Muhsin Ahmad; Rosmah Tami (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This study examines the moral values in Habib Aidarus bin Salem Al-Jufri's poem